Concepts as Assemblages: Methodological Proposal for Critical Discourse Research on Gender Identity - Soich, Matías (2025)
This paper upholds the importance of treating concepts as situated interdisciplinary arrangements or assemblages. This proposal is based on my research on the discursive representation of transgender identities in Buenos Aires, Argentina. I start by giving some context on gender identity as a research topic, and make the case for studying it from a discursive perspective. I then present the methodology, theoretical framework, and main results of my research. From it, gender identity emerges as an interdisciplinary concept that combines elements from Critical Discourse Analysis, Transgender theory, and Deleuzian philosophy. Finally, I use the connections between them to propose a methodological approach based on the concept of assemblage, as a view that can enrich both Discourse Studies in particular and critical social science in general.